Perimenopausal invasive complete hydatidiform mole: a rare encounter (Journal of Pathology of Nepal, 2022)
Invasive mole, classified under the gestational trophoblastic diseases, comprises of hydropic chorionic villi invading the underlying myometrium, blood vessels or extra-uterine sites. They are usually diagnosed clinically and are treated with chemotherapy. Thus, surgery is rarely performed owing to good response to chemotherapy and preservation of fertility, since most women are in reproductive age. Thus, these specimens are rarely encountered by the pathologists. Here, we report a case of invasive mole in a 48 year old female with persistent elevation of serum beta HCG levels and completed family status who underwent hysterectomy and was diagnosed as a case of invasive mole on histopathologic examination.